Cross-Border Deposits and Monetary Aggregates in the Transition to EMU - Angeloni, Ignazio (IMF Working Papers; Working Paper ;, 1991)
This paper discusses the effect of cross-border deposits (CBDs) for the stability of the relation between monetary aggregates and nominal GDP in the five largest EC countries. The analysis is developed in terms of 'information content' of alternative money definitions (including or excluding selected subsets of CBDs), derived from a multicountry simultaneous system of money demand equations. We show that in the most recent period traditional money aggregates have lost information value and that they are dominated by alternative money definitions that include CBDs, such as those based on the residency of the holder or on the currency of denomination.